Severe Acute Pancreatitis Due to Tamoxifen-Induced Hypertriglyceridemia with Positive Rechallenge - Sakhri, Jaballah; Salem, Chaker Ben; Harbi, Houssem; Fathallah, Neila; Ltaief, Rached (JOP. Journal of the Pancreas, 2010)
Context Pancreatitis is a very rare adverse effect of tamoxifen with only six cases of tamoxifen-associated pancreatitis reported in the English literature until now. In these cases, rechallenge with tamoxifen was not carried out. Case report We report a case of recurrent severe acute pancreatitis in a 44-year-old female induced by tamoxifen therapy and review the literature with regards to tamoxifen-associated pancreatitis. Conclusion Clinicians should be aware of the risks of developing severe acute pancreatitis when using tamoxifen therapy. If tamoxifen is suspected as the probable causative agent, rechallenge with this drug should be prohibited. Image: Farhat Hached Hospital. Sousse, Tunisia.